„I am the Absolute Will”. On Divinity of Power in the Ladislav Klíma’s Philosophy - Woźniak, Kamila (Poznańskie Studia Slawistyczne, 2013)
The article concerns philosophical concepts created by the Czech prose writer Ladislav Klíma. This author is nowadays counted among the most interesting Czech philosophers of the 20th century. His concepts inspired creators such as Hrabal or the Czech surrealists. The article’s author presents an outline of more important Klíma’s philosophical concepts, which allow to combine the theme of man’s deification with the divine aspect of power. In the article, a vision of the world and man created by Klíma is presented, which points out a Gnostic character of his philosophical theories. The presentation regarding a definition of freedom, which in Klíma’s depiction is the basis for achieving the divine state, is of an equal importance.